2022
DOI: 10.9745/ghsp-d-21-00426
|View full text |Cite
|
Sign up to set email alerts
|

Improving Iron and Folic Acid Supplementation Among Pregnant Women: An Implementation Science Approach in East-Central Uganda

Abstract: Although iron and folic acid supplementation (IFAS) is a well-known and effective intervention for anemia in pregnant women, its access and uptake were affected by stock-outs and inadequate health education of both health care workers and pregnant women. n An intervention combined enhanced quality improvement (QI) activities with an implementation science approach that resulted in a significant increase in the probability of pregnant women receiving IFAS and health education on IFAS during antenatal care (ANC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Previous research has indicated a similar range of effect during the pandemic based on iron supplementation and IFA interventions 1.39 (0.33, 2.45); P = 0.01* and 0.72 (0.36, 1.07); P < 0.00001 respectively [30]. The general net cumulative effect of the interventions on maternal anemia ranged from 23% to 81% [31]–[33]. This is implicated in past recent studies Additionally, another meta-analysis reported the outcome of interventions on maternal anemia during the COVID-19 pandemic[30].…”
Section: Discussionmentioning
confidence: 88%
“…Previous research has indicated a similar range of effect during the pandemic based on iron supplementation and IFA interventions 1.39 (0.33, 2.45); P = 0.01* and 0.72 (0.36, 1.07); P < 0.00001 respectively [30]. The general net cumulative effect of the interventions on maternal anemia ranged from 23% to 81% [31]–[33]. This is implicated in past recent studies Additionally, another meta-analysis reported the outcome of interventions on maternal anemia during the COVID-19 pandemic[30].…”
Section: Discussionmentioning
confidence: 88%